2014
DOI: 10.1097/jto.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Variation in the ATP-Binding Cassette Transporter ABCB1 and Survival after Chemotherapy for Stage III–IV Lung Cancer

Abstract: Background The ATP-binding cassette transporter gene ABCB1 and the glutathione S-transferase gene GSTP1 code for a multidrug resistance (MDR) protein and for a detoxifying phase II metabolic enzyme, respectively, with substrate specificities that include chemotherapy drugs commonly used to treat lung cancer. Methods We genotyped 11 ABCB1 and 8 GSTP1 single nucleotide polymorphisms (SNPs) in 698 white lung cancer patients (all current or former cigarette smokers) and used log-rank test statistics and proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Although there is evidence of the correlation between ABCB1 expression and treatment response and survival rates in tumour cancer patients (Coyle et al , ; Kim et al , ), we did not find a functional link between ABCB1 ‐rs2235013 and the gene expression. However, Weissfeld et al () reported that carriers of the T allele of ABCB1 ‐rs2235013 showed better lung cancer survival, in agreement with the results of our OS phase but in disagreement with our PFS results. Therefore, even though the results found are difficult to explain, they are potentially interesting also in light of that found in the literature (Weissfeld et al , ; Coyle et al , ; Kim et al , ) and certainly indicate that further investigation on the functional relevance of ABCB1 ‐rs2235013 is needed given its possible role in cancer survival.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Although there is evidence of the correlation between ABCB1 expression and treatment response and survival rates in tumour cancer patients (Coyle et al , ; Kim et al , ), we did not find a functional link between ABCB1 ‐rs2235013 and the gene expression. However, Weissfeld et al () reported that carriers of the T allele of ABCB1 ‐rs2235013 showed better lung cancer survival, in agreement with the results of our OS phase but in disagreement with our PFS results. Therefore, even though the results found are difficult to explain, they are potentially interesting also in light of that found in the literature (Weissfeld et al , ; Coyle et al , ; Kim et al , ) and certainly indicate that further investigation on the functional relevance of ABCB1 ‐rs2235013 is needed given its possible role in cancer survival.…”
Section: Discussionsupporting
confidence: 50%
“…However, Weissfeld et al () reported that carriers of the T allele of ABCB1 ‐rs2235013 showed better lung cancer survival, in agreement with the results of our OS phase but in disagreement with our PFS results. Therefore, even though the results found are difficult to explain, they are potentially interesting also in light of that found in the literature (Weissfeld et al , ; Coyle et al , ; Kim et al , ) and certainly indicate that further investigation on the functional relevance of ABCB1 ‐rs2235013 is needed given its possible role in cancer survival. A recent study (Jakobsen Falk et al , ) investigated the possible role of some ABCB1 SNPs in the outcome of 90 relapsed or refractory MM patients.…”
Section: Discussionsupporting
confidence: 50%
“…Four of these have been investigated for predicting antidepressant response or remission: rs2032583 (7,8,11,34,35), rs2235033 (8), rs2235015 (7,8,11), and rs10245483 (7). Others have been studied in other diseases (e.g., rs10276036, rs2214102, and rs32313619 in cancer risk) (36,37). DNA extraction was performed from EDTA-treated blood using the Puregene DNA method (Qiagen, Valencia, Calif.).…”
Section: Genetic Analysismentioning
confidence: 99%
“…Although a meta-analysis, including 5 studies with a total of 379 Asian and Caucasian patients, reported higher ORR for the CC variant (OR=1.82; CI95%=1.17, 2.85; I 2 =0%; Pheterogeneity=0.77; CC vs CT/TT) [33]. The C-allele has also been associated with better OS (HR=0.77; CI95%=1.11, 6.99 for C vs T allele) and PFS (HR=0.62; CI95%=0.38, 1.00 for C vs T allele) in two studies including 160 and 94 advanced NSCLC patients, respectively [34,109]. A correlation with grade 3-4 gastrointestinal toxicity was also initially reported in 62 stage IIIB-IV NSCLC patients (p=0.03) [79], but in further studies failed to confirm it [35,103,109].…”
Section: Abcb1mentioning
confidence: 97%
“…Genetic alterations in genes of the PI3K/PTEN/AKT and TGF-β pathways may modify signaling and have an impact in the development of toxicity or disease progression to platinum-based therapies [28][29][30][31][32]. Polymorphisms in ATP-binding cassette, sub-family B (MDR/TAP), member 1 (ABCB1, also called MDR1) have also been suggested as predictive markers of response and side effects to platinum therapy [33][34][35]. ABCB1 gene is an cell membrane transporter [36], involved in the ATP dependent export of chemicals out of cell [37][38][39] that modulates response and toxicity by impairing the intracellular retention of multiple anticancer drugs [40,41].…”
Section: Introductionmentioning
confidence: 99%